Plasma C4d Correlates With C4d Deposition in Kidneys and With Treatment Response in Lupus Nephritis Patients - Martin, Myriam; Trattner, Rebecca; Nilsson, Sara C.; Björk, Albin; Zickert, Agneta; Blom, Anna M.; Gunnarsson, Iva (Frontiers in Immunology, 2020)
Objective: To examine whether C4d plasma levels correlate with treatment response and C4d kidney deposition in systemic lupus erythematosus (SLE) with lupus nephritis (LN). Methods: C4d plasma levels were analyzed by a unique assay specifically detecting C4d arising from complement activation and C4 plasma levels were quantified with competitive ELISA. SLE patients with LN (71) and active SLE patients without LN (22) plus 145 controls were included. For 52 LN patients samples were available both at baseline and after immunosuppressive treatment. C4d kidney deposition was detected using immunohistochemistry in two matching kidney biopsies of 12 LN patients. Results: In comparison to population-based controls, plasma C4d levels were significantly increased in SLE patients (0.33 mg/L versus 0.94 mg/ml, p<0.0001) with significantly higher levels in LN patients (1.02 mg/L) than in non-renal SLE patients (0.57 mg/L, p=0.004). The C4d/C4 ratio was also significantly higher in LN (11.2) than in non-renal SLE patients (2.5, p=0.0002). According to ROC curve analysis, C4d was found to be an accurate marker to discriminate LN from non-renal SLE patients (p=0.004). The C4d/C4 ratio displayed even higher specificity, sensitivity and overall accuracy as marker for LN than C4d and C4 alone. At baseline, C4d levels correlated significantly with urine-albumin to creatinine ratio (rs=0.43, p=0.011) and with renal activity index (rs=0.37, p=0.002). Immunohistochemical staining showed glomerular deposits of C4d in kidney biopsies, which strikingly correlated with plasma C4d levels (rs=0.7, p=0.0002). Plasma C4d declined significantly after treatment in patients that experienced favorable clinical and histopathological response (p<0.0001), while levels remained mainly unchanged in non-responders. Conclusion: Plasma C4d discriminates LN from active non-renal SLE, correlates with C4d kidney deposits and appears valuable in monitoring responsiveness to various treatments. The C4d/C4 ratio might be superior to C4d alone.